Effects of Anthropogenic Activities on theWater Quality of River Nyakomisaro-Riana, Kisii, Kenya - Ogendi, George Mokua (European Journal of Applied Sciences, 2022)
Access to safe drinking water is a major challenge to urban populations in developing countries. Most of Kisii town residents draw raw water from rivers and springs for domestic use which is highly contaminated. No water quality assessments in these rivers have been conducted. An assessment was therefore conducted on water quality of River Nyakomisaro-Riana flowing through Kisii town, during May 2013 to October 2014. The overall objective was to to assess the spatial and temporal variation of selected physical, chemical and biological parameters of river Nyakomisaro-Riana. Five sampling sites equidistant from one another were selected to establish a sampling transect for this river. Standard methods described in APHA, 1998 were used to determine levels of physico-chemical parameters, nutrient concentrations and biological characteristics. This study was conducted on this river for the first time and forms a basis for comparison with future studies. Spatial and temporal patterns of the parameters were analyzed and presented in tabular and graphical formats using Excel and Sigma Plot software. Descriptive statistics were done. Analysis of variance and Tukey’s pairwise comparisons were used to establish whether there were significant differences in studied parameters. Results indicated that the concentrations of total dissolved solids, Total supsennded soilds, Electrical conductivity, temperature, total suspended solids increased downstream while dissolved oxygen concentration and pH decreased. The increasing trend of the physico-chemical parameters downstream was attributed to observable anthropogenic inputs via raw sewage disposal into this rivers, car wash sites, garbage dumpsites close to riverbanks and surface run-off from the town catchment. Inflow of pollutants into the river was made worse by unplanned settlements along the riverbank with lots waste disposal facilities, car-wash bays and garages along it. This study recommends that oversight organizations like NEMA, GWASCO, Ministry of Environment and other related organizations take necessary action to improve the water quality of this river.